The Effectiveness of Regional Regulation of The Province of Bali Number 16 of 2009 Concerning Spatial Planning for The Province of Bali in The Development of Tourism Supporting Facilities at The Sanctuary Area in Badung Regency - Ida Ayu Putu Widiati; Luh Putu Suryani; Indah Permatasari (Fakultas Hukum, Universitas Warmadewa, 2020)
One of the highly developed tourism industries in Bali is the tourism industry. Nevertheless, the problem that then arises is that there are developments encountered in the area of the holy place that should not be made as a place to support the tourism facilities. This is of course not in accordance with the provisions of Regional Regulation Number 16 of 2009 concerning Spatial Planning for the Province of Bali, particularly in Article 50 paragraph (2). This study examines the effectiveness of Bali Province Regional Regulation Number 16 of 2009 related to the construction of Tourism supporting facilities in the radius of the shrine area in Badung Regency. The whole data collected are processed and analyzed by organizing them systematically, and are then classified and connected between one data with another. In practice, there are still violations related to the rules of the radius of the sacred area around the Pura Sad Kahyangan, especially in the Pura Luhur Uluwatu. The existence of norms related to sacred areas comes through pros and cons in practice. Some judicial review requests have even been submitted to the Supreme Court. The role of law enforcement also needs necessarily to be optimized, especially in terms of enforcing the rule of law related to violations in the radius of the holy place in the Badung Regency.